The natural history of levator avulsion one year following childbirth: a prospective study. (17th December 2014) - van Delft, KWM; Thakar, R; Sultan, AH; IntHout, J; Kluivers, KB
<x xml:space="preserve">Abstract</x> Objective To explore the natural history of levator avulsion in primipara 1 year postpartum and correlate this to pelvic floor dysfunction (PFD). Design Observational longitudinal cohort study. Setting District General University Hospital. Population or sample Nullipara at 36 weeks of gestation, 3 months and 1 year postpartum. Methods Validated methods assessed muscle strength, prolapse, ultrasound measurements of levator hiatus and avulsion, and questionnaires for sexual function, and urinary and anal incontinence. Pattern differences over time were evaluated using linear mixed models. Main outcome measures Natural history of levator avulsion and relationship with PFD. Results Of the 269 nullipara, 191 returned at 3 months and 147 (55%) at 1 year postpartum; 109 had a vaginal delivery and 38 had a caesarean delivery. Sixty‐two percent (n = 13/21; 95% CI 41–79%) of levator avulsions diagnosed 3 months postpartum were no longer evident at 1 year. Following vaginal delivery, nine women (8%, 95% CI 4.2–15.1%) had persistent levator avulsion. Most changes in PFD occurred between the antenatal and first postnatal visit, without improvement at 1 year. Women with persistent levator avulsion had significantly worse deterioration patterns of muscle strength, hiatus measurements and vaginal symptoms (loose vagina/lump sensation). However, evidence of PFD was also related to no longer evident levator avulsion. Conclusions Sixty‐two percent of levator avulsions were no longer evident 1 year postpartum. Partial avulsion has a tendency to improve over time, which seems to be less common for complete levator avulsions. Women with no longer evident and persistent levator avulsion had PFD, with worse patterns in presence of persistent avulsion.